Electronic relaxation and dissociation dynamics in formaldehyde: pump wavelength dependence. Issue 3 (5th January 2022) - Endo, Tomoyuki; Neville, Simon P.; Lassonde, Philippe; Qu, Chen; Fujise, Hikaru; Fushitani, Mizuho; Hishikawa, Akiyoshi; Houston, Paul L.; Bowman, Joel M.; Légaré, François; Schuurman, Michael S.; Ibrahim, Heide
Abstract : The effect of the incident UV pump wavelength on the subsequent excited state dynamics, electronic relaxation, and ultimate dissociation of formaldehyde is studied using first principles simulation and Coulomb explosion imaging (CEI) experiments. Abstract : The effect of the incident UV pump wavelength on the subsequent excited state dynamics, electronic relaxation, and ultimate dissociation of formaldehyde is studied using first principles simulation and Coulomb explosion imaging (CEI) experiments. Transitions in a vibronic progression in the Ã ← X̃ absorption band are systematically prepared using a tunable UV source which generates pulses centered at 304, 314, 329, and 337 nm. We find, both via ab initio simulation and experimental results, that the rate of excited state decay and subsequent dissociation displays a prominent dependence on which vibronic transition in the absorption band is prepared by the pump. Our simulations predict that nonadiabatic transition rates and dissociation yields will increase by a factor of >100 as the pump wavelength is decreased from 337 to 304 nm. The experimental results and theoretical simulations are in broad agreement and both indicate that the dissociation rate plateaus rapidly after ≈2 ps following an ultrafast sub-ps rise.